Religiosity and Spirituality in Military Veteran Cancer Survivors: A Qualitative Perspective - Trevino, Kelly M. (J Psychosoc Oncol, 2011)
Religiosity/spirituality (R/S) is often involved in coping with cancer. Qualitative research effectively captures the individuality of R/S constructs. Fourteen military veteran cancer survivors participated in focus groups. R/S questions included “How have your religious/spiritual beliefs affected how you cope with your cancer” and “How have your religious/spiritual beliefs changed as a result of your experience with cancer?” Five primary themes emerged: impact of cancer on R/S, meaning-making, prayer, religious/spiritual role of others, and facing death. Consistency and individuality characterized the role of R/S in cancer survivorship across themes. Implications for future research are discussed.